THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE EDUCATION SYSTEM - Haqberdiyev Bahrom Bobonazarovich (American Journals, 2026)
This scientific article provides a comprehensive analysis of the role, significance, and development prospects of artificial intelligence (AI) technologies in the modern education system. Within the context of digital education, the opportunities for individualized instruction based on AI, automated knowledge assessment, monitoring of the educational process, and optimization of pedagogical activity are examined. Furthermore, the challenges arising during the implementation of AI technologies in the education system and scientifically grounded solutions to overcome them are discussed.
Keywords: Artificial intelligence, digital education, individualized learning, automated assessment, education system, innovative technologies.